2019
DOI: 10.1159/000502138
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease Assessed by Computed Tomography in Patients with Psoriasis: A Systematic Review and Meta-Analysis

Abstract: Background: Patients with psoriasis have an increased risk of coronary artery disease (CAD) but data on coronary calcium score (CCS) and cardiac computed tomography angiography (CCTA) are inconsistent. Objectives: The present study quantitatively summarizes the literature data on the prevalence and burden of CAD in patients with psoriasis compared with controls using CCS and CCTA. Methods: A systematic review and meta-analysis was conducted. The search included all studies examining CAD prevalence and burden d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…However, a coronary calcium score > 400 was more frequently observed in patients with severe psoriasis, even adjusting for the risk estimated by the Framingham score [ 74 ]. Recently, a systematic review and meta-analysis showed that the patients with psoriasis had an increased risk of coronary calcium score > 0 (RR 1.14, 95% CI 1.04–1.26; p = 0.004) and > 100 (RR 1.71, 95% CI 1.28–2.30; p < 0.001) compared with controls [ 75 ].…”
Section: Stratification Of Cardiovascular Riskmentioning
confidence: 99%
“…However, a coronary calcium score > 400 was more frequently observed in patients with severe psoriasis, even adjusting for the risk estimated by the Framingham score [ 74 ]. Recently, a systematic review and meta-analysis showed that the patients with psoriasis had an increased risk of coronary calcium score > 0 (RR 1.14, 95% CI 1.04–1.26; p = 0.004) and > 100 (RR 1.71, 95% CI 1.28–2.30; p < 0.001) compared with controls [ 75 ].…”
Section: Stratification Of Cardiovascular Riskmentioning
confidence: 99%
“…Coronary computed tomography angiography (CCTA) is a non-invasive technique that gives direct anatomic visualization of the coronary artery wall, reliably measures the overall plaque burden, size and severity of luminal restriction [24], and identifies vulnerable, lipid-rich plaques with a high likelihood of rupture leading to an acute coronary syndrome [25]. Despite that patients with PsD have an increased risk of CAD compared with controls [17,26], there are limited data available on CAD as assessed by CCTA in this population. Hjuler and colleagues compared prevalence, severity, and subtypes of coronary plaques between patients with severe psoriasis, atopic dermatitis (AD), and asymptomatic controls without known CVD.…”
Section: Coronary Ct Scansmentioning
confidence: 99%
“…In a systematic review and meta-analysis, Kaiser et al , based on the analysis and summary of results of 14 studies involving cardiac computed tomography, showed that patients with psoriasis more often suffered from coronary artery disease, with higher CS values and a greater number of unstable atherosclerotic plaques than the healthy population [ 43 ].…”
Section: Discussionmentioning
confidence: 99%